2010
DOI: 10.1016/j.ejvs.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of the Magnitude and Direction of Migration Forces in Patient-specific Abdominal Aortic Aneurysm Stent-Grafts

Abstract: Numerical methods can be used to determine patient-specific drag forces which may help determine the likelihood of stent-graft migration. Anterior-posterior neck angulation appears to be the greatest determinant of drag force magnitude. Graft dislodgement may occur anteriorally as well as caudally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 27 publications
(33 reference statements)
7
81
1
Order By: Relevance
“…It is becoming increasingly clear that evaluating the simple downward (y-direction) force acting on the device is not sufficient, and that the out-of-plane forces play an important role [18,40]. Our group is presently evaluating the out-of-plane configuration of crossed-limb stent-grafts.…”
Section: Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It is becoming increasingly clear that evaluating the simple downward (y-direction) force acting on the device is not sufficient, and that the out-of-plane forces play an important role [18,40]. Our group is presently evaluating the out-of-plane configuration of crossed-limb stent-grafts.…”
Section: Future Workmentioning
confidence: 99%
“…Our group is presently evaluating the out-of-plane configuration of crossed-limb stent-grafts. Given that the recent studies indicate that forces in the anterior direction are significant [18,40], our group plans to carry out experimental studies to determine pullout forces at various anterior and lateral angulations. These would be important contributions to the understanding of stent-grafts, and the experimental studies could serve as references against which predicted forces from simulations could be compared.…”
Section: Future Workmentioning
confidence: 99%
“…It was shown that aortic geometry presents curvature, angulations, and tortuosity that influence the magnitude and, most importantly, the direction of displacement forces, which are directed not only caudally, but rather anterolateraly or even cephalad. [12][13][14] This has clear implications for modifying the design of endovascular grafts, such as the enhancement of central fixation with suprarenal hooks and barbs or the accommodation of endografts onto the aortic bifurcation, which sustains the greatest percentage of displacement forces. 15 Computational studies can provide significant information on the importance of different geometrical features of endografts (angulation, curvature, tortuosity, length or diameter ratios of the different segments) on the risk of migration, overcoming several difficulties and limitations that clinical comparative studies would encounter in drawing similar conclusions.…”
Section: Biomechanical Approach Of Aortic Stent-grafts: What Is To Bementioning
confidence: 99%
“…Interventional cardiovascular catheterization, such as stent and coiling are both of the advances to treat aneurysms [6][7][8], should stay in the body and have some complications, such as the displacement of the stent and the coil fall off from the aneurysm [9,10]. Considering the blood coagulation induced by the heating of radiofrequency ablation (RFA), the mechanism of aneurysm embolization and the advantages of simple operation, small trauma, low cost, faster recovery, high success rate, etc [11][12][13][14][15] , Qiao, et al proposed that RFA may be used to treat aneurysm by combining the mechanism of blood coagulation of RFA and aneurysm embolization [16].…”
Section: Introductionmentioning
confidence: 99%